Stride of Service Sector in Nepal’s Trajectories of Structural Change - Dahal, Madhav Prasad (Economic Journal of Development Issues, 2018)
Agriculture, manufacturing and service sectors are the major economic sectors of a country. The long held view is that economies’ development trajectories move from agriculture to manufacturing to services. These conclusions are primarily based on the studies of developed countries. However more recent studies relating to developing countries have brought evidences that the structural transformation path is not linear as experienced by today’s developed countries. Nepal is not an exception is experiencing the waves of sector-wise structural transformation. Using time series data of the period 1975-2016 of the economy of Nepal this paper analyses the association between gross value added and service sector value added in the analytic-framework of the autoregressive distributed lag (ARDL) to cointegration. The empirical result reveal a cointegrating relationship between real gross value added and service sector value added. Result also show service sector enhancing role of education and export trade of Nepal. The paper finally draws few policy implications essential for service sector sustainability to support overall economic growth. Economic Journal of Development Issues Vol. 21 & 22 No. 1-2 (2016) Combined Issue